Magnetohydrodynamic mixed convection within a ventilated cavity crossed by a nanofluid: Effect of the obstacle position - Moderres, Mourad; Kherroubi, Seddik; Boutra, Abdelkader; Settar, Abdelhakim; Ghenai, Chaouki; Azzouzi, Djelloul; Öztop, Hakan Fehmi (Yildiz Technical Univ, 2026)
This study presents a numerical investigation into mixed convection heat transfer within a ventilated square cavity containing a circular obstacle, evaluated under various magnetic field inclination angles. Ventilation is ensured by two fixed openings on the vertical walls of the cavity. Cold Carbon Nanotubes-water nanofluid enters through the opening at the top of the left vertical wall and exits through the opening located at the bottom of the right vertical wall. All four walls of the cavity are maintained at the same temperature, which is higher than that of the incoming nanofluid. The finite volume method, combined with the SIMPLER algorithm for pressure-velocity coupling, was utilized to solve the governing differential equations of the system. The objective was to determine the optimal geometry that offers the best thermal performance with the lowest pressure drop. Key results indicate that increasing the nanoparticle volume fraction from 0% to 6% enhances the average Nusselt number by up to 20.3%, significantly improving heat transfer performance. Similarly, tilting the magnetic field at an angle of 45 degrees minimizes the pressure drop by 12% compared to the baseline case. The optimal obstacle position was identified as the cavity center, balancing heat transfer enhancement with a manageable pressure drop. These findings can be applied to optimize the design of cooling systems in industrial applications such as electronic device cooling, energy storage systems, and heat exchangers, where efficient thermal management and minimal pressure loss are crucial. The research introduces a new application of Carbon Nanotubes-water nanofluid to enhance heat transfer performance, with the added complexity of a magnetic field influencing the flow dynamics.
Keywords: Circular Obstacle; Magnetic Field; Mixed Convection; Nanofluids; Ventilated Cavity